Cloud Security: Challenges and Future Scope (International Journal of Innovative Research in Engineering & Management, 2023)
Now Cloud computing becomes so much  popular coz satisfying business needs efficiently. Cloud  features provide best lead to organizations to effectively  access data and services with less cost over the internet. This  also raise issues related with cloud security. This paper  presents brief information regarding cloud computing  security challenges. This information includes security  mechanisms that should be consider for Cloud Service  Models. This Work also focus on detail knowledge of  security issues, threats which may use by attacker. It also  explains cloud components levels threats and attack so more  secure mechanism can identified for each component. This  Paper introduced classification of Cloud security areas issues  to develop secure Cloud Security services in future.
Keywords: Cloud Computing; Cloud Security; Threats; Security issues; Data protection; Attacks